Various approaches for targeting colon: a review - Raghuvanshi, Neha Singh; Goswami, Laxmi; Kothiyal, Preeti (Journal of Applied Pharmaceutical Research, 2014)
The colonic region of GIT has become an increasingly important site for drug delivery and absorption. This site specific delivery of drug to lower parts of the GIT is advantage for localized treatment of several colonic disease like colon cancer, crohn’s disease, ulceratice colitis, IBD, diarrhea etc. colon targeted drug delivery system (CTDDS) ensure direct treatment at the disease site and avoiding the systemic side effects. It is suitable for absorption site for protein and peptide drugs. Cytochrome P450 3A class of drug metabolizing enzyme, have lower activity in colon. This review, mainly compares the primary approaches for (CTDDS) Colon targeted Drug Delivery system namely prodrugs, pH and time dependent systems, and microbially triggered systems, which achieved limited success and had limitations as compared with newer CDDS namely pressure controlled colonic delivery capsules, CODESTM, and osmotic controlled drug delivery which are unique in terms of achieving in vivo site specificity, and feasibility of manufacturing process